Biblical Studies in Poland in the Context of Current Tendencies - Wrobel, Miroslaw Stanislaw (The Biblical Annals, 2019)
Report: Biblical Studies in Poland in the Context of Current Tendencies. SBL Meeting, Berlin, 7-11 of August, 2018